2023
DOI: 10.1017/s0007114523000314
|View full text |Cite
|
Sign up to set email alerts
|

Serum folate mediates the associations of MTHFR rs1801133 polymorphism with blood glucose levels and gestational diabetes mellitus in Chinese Han pregnant women

Abstract: This study aimed to explore the mediation effects of one-carbon metabolism (OCM) related nutrients on the association between MTHFR rs1801133 polymorphism and gestational diabetes mellitus (GDM). Folate, vitamin B12 (B12), and homocysteine (Hcy) were measured in the serum of 1254 pregnant women. Linear and logistic regressions were used to estimate the associations of OCM nutrients and MTHFR rs1801133 polymorphism with blood glucose levels and GDM risk. Mediation analysis was applied to test the mediation effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…WHO guidelines do not recommend promoting MMFA in pregnant women due to insufficient evidence of its benefits for neonatal survival, growth, or cognitive function compared to FAO. Additionally, MMFA supplementation may pose an increased economic burden for pregnant women (9). Although we did not investigate the specific nutrient contents and doses of MMFA, our results support prioritizing FAO supplementation for GDM prevention.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…WHO guidelines do not recommend promoting MMFA in pregnant women due to insufficient evidence of its benefits for neonatal survival, growth, or cognitive function compared to FAO. Additionally, MMFA supplementation may pose an increased economic burden for pregnant women (9). Although we did not investigate the specific nutrient contents and doses of MMFA, our results support prioritizing FAO supplementation for GDM prevention.…”
Section: Discussionmentioning
confidence: 69%
“…The findings indicated that MMFA supplementation primarily affected FPG levels, increasing the risk of developing GDM. Previous studies have demonstrated a relationship between vitamin B12 levels and FPG; however, no significant associations were observed between vitamin B12 and either 1 h PG or 2 h PG ( 10 ). This may suggest that FPG serves as a more sensitive indicator for GDM diagnosis and predicting risk factors.…”
Section: Discussionmentioning
confidence: 85%
“…The study design has been described in our previous studies. 6 , 10 In brief, a total of 1505 pregnant women who underwent GDM screening between 24–28 weeks of gestation were recruited according to the following criteria: (1) older than 18 years; (2) have lived in Tianjin for one year and plan to live in Tianjin for the next six years (3) have no history of pre-pregnancy diabetes or previous GDM. Of the 1505 pregnancies, 202 were excluded for various reasons, such as being from ethnic minorities (n = 105), not having GDM (n = 38) and OCM results (n = 33), and missing covariate results (n = 26).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…3 Recent studies have shown that environmental pollutants (such as arsenic and air pollution) and nutrients involved in the one-carbon metabolism (OCM) pathway may be essential in GDM. [6][7][8][9][10] Our previous study indicated that genetic variants in N-6-adenine-specific DNA methyltransferase 1 (N6AMT1) were associated with arsenic methylation metabolism. In addition, they can interact to affect GDM occurrence in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the MTHFR gene C677T polymorphism is closely related to the risk of diabetes mellitus (DM) ( 14 , 15 ). Some investigators also revealed that the C-T mutation in the MTHFR C677T gene might lead to increased susceptibility to GDM ( 16 , 17 ). However, whether the MTHFR gene C677T polymorphism leads to an increased risk of GDM in the Chinese population remains controversial.…”
Section: Introductionmentioning
confidence: 99%